Perancangan Sistem Pencatatan Berbasis Website pada Posyandu RT 004 RW 011 Kelurahan Kramat Jati - Nendi; Pradita, Anggi; Nurrohman, Awaludin Taufiq; Badzlin, Rosyiqoh (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2024)
Within the scope of this service, the focus is on the urgent needs of Posyandu as the foundation of community health services related to implementing a more efficient recording and reporting system. The main challenge arises from manual recording methods using Microsoft Excel at Posyandu Cempaka 3 RT 004 RW 011 Kramat Jati, East Jakarta, which hinders the reporting process to the health center. As a solution, the proposed development of a web-based information system for recording aims to improve the administrative efficiency of Posyandu. This service adopts the waterfall method in designing an efficient web-based recording information system. The result is a prepared web application interface for implementation, expected to overcome manual recording constraints and support timely reporting to the health center. Thus, the use of information technology in Posyandu recording is expected to contribute positively to the smooth administration and quality of local community health services, creating a solid foundation for monitoring and improving the health of mothers and children.